TRANSFORMATIONAL LEADERSHIP STYLE, LEVERS OF CONTROL, AND UNIVERSITY PERFORMANCE: Case Study at Ciputra University - Eka, Silvester Dimas (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2021)
Competition are tight on education is going on, due to changes in the environment. There are 130 private universities that stopped operating in 2015-2019. As the youngest university in East Java and accredited A, Ciputra University is able to pass the competition well. The purpose of this study was to determine the direct effect of transformational leadership on the performance of Ciputra University and the indirect effect through levers of control as a mediating variable. Research sample namely 40 Ciputra University officials including Heads of Departments, Heads of Study Programs, Deans, Chancellors, and Vice Chancellors. Data collection with primary data through spreading quistionnaire. Data analysis was performed using Structural Equation Modeling. The results of the study prove that transformational leadership has an effect on levers of control and university performance. The application of levers of control has a positive effect on university performance, as well as leadership styles that have a positive effect on university performance through levers of control.